Determination of morphological and functional adaptations in top level female handball players using cardiac MR imaging - Kramer, U.; Mangold, S.; Krumm, P.; Seeger, A.; Franzen, E.; Niess, A. M.; Claussen, C. D.; Burgstahler, C. (Deutsche Zeitschrift für Sportmedizin, 2013)
Rationale and Objectives: Long-term physical training is associated with morphological and functional adaptations of the cardiovascular system. Aim of this prospective study was to assess physiologic adaptations and structural cardiac remodelling and to analyze the presence and distribution of myocardial Late Gadolinium Enhancement (LGE) by cardiac magnetic resonance imaging (MRI). Materials and Methods: Thirteen female professional handball players (mean age 25.1±4.7) and 13 age- and gender-matched non-athlete controls (mean age 25.5±4.2) underwent cardiac MRI at 1.5T. Steady-state free-precession cine MRI was used to calculate left and right ventricular end-diastolic volume (EDV), endsystolic volume (ESV), stroke volume (SV), ejection fraction (EF), myocardial mass (MM) and cardiac remodeling index (RI). Macroscopical structural alterations or myocardial scar were excluded by late gadolinium enhancement (LGE) imaging. Results: Indexed LV-EDV and RV-EDV were significantly (P<.001) increased in athletes compared to controls. There was no difference in LV-EF of athletes (61.1±3.3 %) and controls (62.5±5.0%). The LV-RI of athletes (0.65±0.07g/ml) was similar to those of the control subjects (0.64±0.06 g/ml). Neither subendocardial nor midwall myocardial LGE, indicating replacement scarring or interstitial fibrosis, were observed. Discussion and Conclusion: Physical exercise is associated with enlargement of LV and RV chamber size, MM and increased SV in comparison to healthy individuals. MRI enables direct, objective measurement of these features and therefore may allow differentiating them from hypertrophic cardiomyopathy. While no LGE was identified, study results confirm the existence of a balanced mild myocardial hypertrophy and ventricular dilatation in athletes. Based on our results, eccentric LVH in the absence of cardiovascular symptoms has to be judged as a benign phenomenon in these elite athletes, representing a physiologic adaptation to intense exercise training.